The Optics and Photonics of Two-Dimensional Nanomaterials - O'BRIEN, STEPHEN ADRIAN (Trinity College Dublin. School of Physics. Discipline of Physics, 2020)
In this work, by using a broadspectrum angle-resolved absorption technique, we studied enhanced absorption from multi-layered materials with near-zero dielectric permittivity in the near-infrared. These materials, known as epsilon-near-zero (ENZ) materials, are known to exhibit novel physics, including perfect absorption. We demonstrate, both theoretically and experimentally, the excitation of two plasmon modes in indium tin oxide thin-films, a bulk plasmon mode, know as the "Ferrell-Berreman mode" and a long-range surface plasmon polariton mode known as the "non-radiative ENZ mode". These modes result in significant absorption from deeply subwavelength ITO thin-films of thickness 127 nm which is enhanced from a value of 52.5% to values >95% by depositing a 10 nm layer of Pt on the ITO layer as a backing. We observed this near-perfect absorption (NPA) from exciting both modes and studied the dependence of the absorption on the thickness of the Pt backing layer. We observed an asymptotic increase in the absorption maximum with increased Pt backing thickness. Furthermore, we numerically and analytically studied the excitation of these modes, with and without a backing of various metals and of various thicknesses. We found that any common metal can be used to achieved near-perfect absorption by depositing on ITO and exciting these plasmon modes, however the thickness at which the maximum absorption can be achieved is dependent on the complex refractive index and the skin depth of each metal. We also found that there is a maximum in the non-radiative ENZ mode absorption when the metal backing is sufficiently thin so as to allow the excitation of an insulator-metal-insulator (IMI) mode, where two long-range surface plasmons, on the upper and lower surfaces of the metal, are coupled together with the ENZ mode to result in near-perfect absorption. Finally, we studied the suitability of high aspect ratio two-dimensional (2D) nanoflakes of hexagonal boron nitride (h-BN) produced by Liquid Phase Exfoliation (LPE) as a 2D material to deposit on our ITO-Pt structures. As these nanoflakes are produced in aqueous suspensions and tend to form high-scattering surfaces when deposited on solid substrates, we characterised the scattering from these nanoflakes in aqueous suspension using a diffuse scattering intensity path-length resolved technique. We considered several models to describe the scattering from these highly anisotropic nanoflakes and found that the Two-Stream Approximation to the Radiative Transfer Equation best described the scattering form such flakes. Furthermore, we devised an in-situ technique to estimate the lateral size of these particles by direct comparison with polystyrene (PS) nanospheres of similar diameter. However, we found that these nanoflakes are not suitable for coupling with ENZ materials as the highly irregular size and shape led to a dominance of scattering in the optical response.
APPROVED
Keywords: photonics; epsilon-near-zero; plasmonics; physics; 2D materials; nanoscience; metamaterials; nanomaterials